2019
DOI: 10.32553/ijmbs.v3i5.265
|View full text |Cite
|
Sign up to set email alerts
|

“Comparison of a Rapid Semi-Quantitative Latex Agglutination Slide Method Against Quantitative Particle Enhanced Turbidimetric Immunoassay for Measurement of C- Reactive Protein”

Abstract: Serum C -reactive protein (CRP) is an acute phase marker in humans that is useful for the diagnosis and monitoring of inflammatory disease. CRP measurement also helps in differential diagnosis, in the management of neonatal septicaemia and meningitis where standard microbiological investigations are very much timeconsuming. Reliable method (Automated particle enhanced turbidimetric immunoassay) are preferable for routine evaluation of human serum CRP levels. Using such expensive methods in health centres in ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Positive results are obtained at a CRP serum concentration above 6mg/L. 23,24 Alpha-1-antichymotrypsin (ACT) Assays were carried out by a sandwich enzymelinked immunosorbent assay (ELISA) technique using reagents provided by EIAab Science Co. Ltd. (A1710 Guangguguoji, East Lake Hi-Tech Development zone, China). Antibody specific for ACT has been pre-coated onto a microplate.…”
Section: Crp Assaymentioning
confidence: 99%
“…Positive results are obtained at a CRP serum concentration above 6mg/L. 23,24 Alpha-1-antichymotrypsin (ACT) Assays were carried out by a sandwich enzymelinked immunosorbent assay (ELISA) technique using reagents provided by EIAab Science Co. Ltd. (A1710 Guangguguoji, East Lake Hi-Tech Development zone, China). Antibody specific for ACT has been pre-coated onto a microplate.…”
Section: Crp Assaymentioning
confidence: 99%
“…[4] Various studies have shown that raised CRP has high sensitivity, specificity, positive and negative predictive values for neonatal sepsis. [5,6] This study was conducted to determine the sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of CRP in neonates with sepsis in comparison with blood culture. It also aimed to study the association of CRP with blood culture results in the evaluation of neonatal sepsis.…”
Section: Introductionmentioning
confidence: 99%